The new existentialism - Griffin, Tim 19XX- (Les presses du réel, 2017)
In the face of radical transitions in social organization, technology, and the living environment, numerous thinkers have moved away from semiotic and psychoanalytic critical models in order to question human agency and imagine a broader material one existing in the world. Yet the language attending such endeavors?often put forward in the spirit of ?scientific? or ?objective? exercise?suggests we would benefit from revisiting another era's interrogations of rationalism to engage the dilemmas of our own time.0The New Existentialism takes stock of contemporary art in light of these philosophical dialogues, proposing how the tenuous human subject is again faced with the prospect of defining its parameters and context in order to arrive at different terms for ethical thinking, conduct, and meaning.0Edited with a preface by curator and author Tim Griffin, The New Existentialism follows on from the eponymous conference organized at The Kitchen in the context of the ART2 festival in New York in April 2014
Keywords: Existenzialismus; Kunst; Existentialism in art / Congresses; Art and philosophy / Congresses; Konferenzschrift -- New York, NY -- 2014